2020
DOI: 10.1519/jsc.0000000000002258
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Intersession Reliability of Heart Rate Variability—The Effects of Artifact Correction and Breathing Type

Abstract: This study aimed to comprehensively investigate the reliability of multiple heart rate variability (HRV) parameters, and to explore the influence of artefact removal and breathing condition on HRV reliability. Resting HRV was collected using Polar Team monitors on forty-one participants (age: 19.9±1.2 years; 28 females, 13 males) during two separate days. Within each session, participants performed 10 minutes each of spontaneous and controlled breathing (randomized order). Kubios HRV analysis software was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…HRV analysis is a widely available and accurate non-invasive technique used as a quantitative assessment tool of the autonomic nervous system (ANS) function. 30 Studies have shown that reduced HRV indices, as assessed by the RR interval analysis, is associated with increased cardiovascular morbidity and mortality in patients with various diseases as well as in the general population. 31 In addition, heart rate and HRV analysis have been used for estimation of mental stress and athlete's fi tness levels, fatigue and overload.…”
Section: Hrv Fundamentalsmentioning
confidence: 99%
“…HRV analysis is a widely available and accurate non-invasive technique used as a quantitative assessment tool of the autonomic nervous system (ANS) function. 30 Studies have shown that reduced HRV indices, as assessed by the RR interval analysis, is associated with increased cardiovascular morbidity and mortality in patients with various diseases as well as in the general population. 31 In addition, heart rate and HRV analysis have been used for estimation of mental stress and athlete's fi tness levels, fatigue and overload.…”
Section: Hrv Fundamentalsmentioning
confidence: 99%
“…We observed an improvement in BRS during controlled breathing that was specific to ST; the magnitude of this improvement was positively associated to the gains in inhibition. The fact that this observation was limited to controlled breathing is probably due to the fact that breathing frequency influences significantly cardiac autonomic control [ 92 ] and its reproductibility [ 93 95 ]. Therefore, controlling breathing frequencey reduces physiological noise, improves the signal-to-noise ratio and in fine increases statistical power, which is of great importance in our study if we consider the relatively small sample size.…”
Section: Discussionmentioning
confidence: 99%
“…First hour of recording therefore was eliminated uniformly across all samples to account for sleep latency and to minimize artifacts related to physical movement and missing data due to malfunctioning devices. A sample size of 4 h was used regardless of sleep onset and phases to reflect sleep cycles and in a similar approach to previous studies (Finley and Nugent, 1995;Goto et al, 1997;Herzig et al, 2017;Jawabri and Raja, 2020), Kubios artifact correction algorithm with medium threshold was utilized to remove artifacted waveforms automatically (Gisselman et al, 2020), R-R time series interpolation rate of 4 HZ was used.…”
Section: Cardiac and Autonomic Functionmentioning
confidence: 99%